2019
DOI: 10.26905/jkdp.v23i2.2687
|View full text |Cite
|
Sign up to set email alerts
|

The differences between family firms and non-family firms: Evidence in Indonesia

Abstract: A family firm is a firm controlled by members of a family through their ownership in the management. This study aimed to observe the presence of differences in gender diversity, cash holding, and financial performance on Family Firms (FFs) and Non-Family Firms (NFFs). The purposive sampling conducted in this study produced 67 samples of companies listed on the Compass 100 Index. They mostly belong to the FF criteria. They also have gender diversity, non-conservative capital structure, medium-size, and low cash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…There have been relatively few studies on dividend policy in family firms in Indonesia. Kristanti et al (2019), by examining family firms belonging to the Kompas 100 stock index in 2013-2016, found that cash holding, firm size, leverage, and profitability in family firms have a significant and negative effect on dividend policy, and firm size has no significant effect on dividend policy. In addition, Atmaja (2016) examined public firms in 2002-2009 and found that family control has a negative effect on dividend payments.…”
Section: Figure 1 Average Dividend Payout Ratio (Dpr) In Family Firmsmentioning
confidence: 99%
See 4 more Smart Citations
“…There have been relatively few studies on dividend policy in family firms in Indonesia. Kristanti et al (2019), by examining family firms belonging to the Kompas 100 stock index in 2013-2016, found that cash holding, firm size, leverage, and profitability in family firms have a significant and negative effect on dividend policy, and firm size has no significant effect on dividend policy. In addition, Atmaja (2016) examined public firms in 2002-2009 and found that family control has a negative effect on dividend payments.…”
Section: Figure 1 Average Dividend Payout Ratio (Dpr) In Family Firmsmentioning
confidence: 99%
“…The Debt to Equity Ratio (DER) reflects the firm's ability to meet all of its obligations and shows how much capital is used to pay off their debts by showing how much capital is used to pay the debts (Kristanti et al, 2019). The higher the DER, the greater the fulfillment of obligations by the firm.…”
Section: Leveragementioning
confidence: 99%
See 3 more Smart Citations